Fiber density of collagen grafts impacts rabbit urethral regeneration - Larsson, H.M.; Vythilingam, G.; Pinnagoda, K.; Vardar, E.; Engelhardt, E.M.; Sothilingam, S.; Thambidorai, R.C.; Kamarul, Tunku; Hubbell, J.A.; Frey, P. (Nature Publishing Group, 2018)
There is a need for efficient and "off-The-shelf" grafts in urethral reconstructive surgery. Currently available surgical techniques require harvesting of grafts from autologous sites, with increased risk of surgical complications and added patient discomfort. Therefore, a cost-effective and cell-free graft with adequate regenerative potential has a great chance to be translated into clinical practice. Tubular cell-free collagen grafts were prepared by varying the collagen density and fiber distribution, thereby creating a polarized low fiber density collagen graft (LD-graft). A uniform, high fiber density collagen graft (HD-graft) was engineered as a control. These two grafts were implanted to bridge a 2 cm long iatrogenic urethral defect in a rabbit model. Histology revealed that rabbits implanted with the LD-graft had a better smooth muscle regeneration compared to the HD-graft. The overall functional outcome assessed by contrast voiding cystourethrography showed patency of the urethra in 90% for the LD-graft and in 66.6% for the HD-graft. Functional regeneration of the rabbit implanted with the LD-graft could further be demonstrated by successful mating, resulting in healthy offspring. In conclusion, cell-free low-density polarized collagen grafts show better urethral regeneration than high-density collagen grafts.